2018
DOI: 10.1111/epi.14481
|View full text |Cite
|
Sign up to set email alerts
|

Place of neurosteroids in the treatment of status epilepticus

Abstract: The treatment of refractory or super-refractory status epilepticus (SE) currently relies on low-evidence strategies, including general anesthetics to induce pharmacologic coma, ketogenic diet, immunosuppression, and other physical measures. Besides the formal uncertainty regarding efficacy, concerns have been about tolerability. In this situation, identification of alternative, higher evidence treatments is urgently needed. Allopregnanolone is an endogenous neurosteroid exerting a positive allosteric modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Initial studies showed that BX was well tolerated and moderately successful at weaning from anesthetic third-line agents. Despite its promise as a therapeutic anticonvulsant, further evaluation of BX in SRSE trials did not meet the primary endpoint, primarily due to its lack of efficacy in controlling seizures and achieving satisfactory outcomes in a clinical setting ( Rossetti, 2018 ). Other contributing factors included the poor prognosis of SRS and high mortality and morbidity rates, as well as challenges with study design and inclusion of heterogeneous patient populations.…”
Section: Neurosteroids As Novel Anticonvulsants For Nerve Agents and Rsementioning
confidence: 99%
“…Initial studies showed that BX was well tolerated and moderately successful at weaning from anesthetic third-line agents. Despite its promise as a therapeutic anticonvulsant, further evaluation of BX in SRSE trials did not meet the primary endpoint, primarily due to its lack of efficacy in controlling seizures and achieving satisfactory outcomes in a clinical setting ( Rossetti, 2018 ). Other contributing factors included the poor prognosis of SRS and high mortality and morbidity rates, as well as challenges with study design and inclusion of heterogeneous patient populations.…”
Section: Neurosteroids As Novel Anticonvulsants For Nerve Agents and Rsementioning
confidence: 99%
“…By binding to both types of GABA A receptors, ganaxolone can potentiate both phasic and tonic inhibition 32 . Neuroactive steroids, such as ganaxolone, have the potential to increase GABAergic signaling when synaptic GABA A receptors are internalized and benzodiazepines are less effective, such as in RSE 35 …”
Section: Introductionmentioning
confidence: 99%
“…32 Neuroactive steroids, such as ganaxolone, have the potential to increase GABAergic signaling when synaptic GABA A receptors are internalized and benzodiazepines are less effective, such as in RSE. 35 In multiple preclinical seizure models, including treatment-resistant SE, ganaxolone exhibited was considered related to ganaxolone; all occurred 9-22 days after completing ganaxolone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of this may be related to inherent difficulties when comparatively studying antiseizure medications, but it bears repeating that potential economic gains for the pharmaceutical industry to develop new medications specifically aimed at status epilepticus are low . Unfortunately, recent studies exploring the efficacy of allopregnanolone for super refractory status epilepticus and hypothermia for neuroprotection in GCSE did not demonstrate improved outcomes, but it is these types of novel pathophysiological studies that are sorely needed in status epilepticus research.…”
mentioning
confidence: 99%